Brushy Brush! - Posner-Sanchez, Andrea; Ferraro, Christine; Roberts, Paul, (Illustrator) (New York : Random House, 2024)
"This lively board book shows kids the right way to brush with some help from Elmo and friends"--.
Cover title.
On board pages.
At head of title: 123 Sesame Street.
"Inspired by the song "Brushy Brush" by Christine Ferraro"--Page 4 of cover.
new kids book 2024 spring.
Keywords: Elmo -- (Fictitious character from Henson) -- Juvenile fiction; Teeth -- Care and hygiene -- Juvenile fiction